Influence of surrounding wall thickness on the fatigue resistance of molars restored with ceramic inlay - Shizuma Shibata; Renata Gondo; Élito Araújo; Carlos Rodrigo De Mello Roesler; Luiz Narciso Baratieri (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The purpose of this study was to evaluate the influence of buccal and lingual wall thickness on the fatigue resistance of molars restored with CAD/CAM ceramic inlays. Forty human third molars were selected and divided into 4 groups, according to the remaining surrounding wall thickness chosen for inlay preparation (n = 10): G1, 2.0 mm; G2, 1.5 mm; G3, 1.0 mm; G4, 0.5 mm. All inlays were made from feldspathic ceramic blocks by a CAD/CAM system, and cemented adhesively. After 1 week stored in distilled water at 37 °C, the specimens were subjected to fatigue testing under the following protocol: 5Hz; pre-load of 200 N for 5,000 cycles, followed by increasing loads of 400, 600, 800, 1000, 1200 and 1400 N for 30,000 cycles each. The specimens were cycled until failure or completion of 185,000 cycles. The survival rate of the groups was compared using the Kaplan-Meier survival curves (p > 0.05). All specimens withstood the fatigue protocol (185,000 cycles), representing a 100% survival rate. The Kaplan-Meier survival curves showed no difference between groups. It can be concluded that the remaining tooth wall thickness did not influence the fatigue resistance of molars restored with CAD/CAM ceramic inlays.